2013
DOI: 10.1634/theoncologist.2012-0373
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Breast Cancer Care and Outcomes in Latin America

Abstract: This review presents an overview of breast cancer care, burden, and outcomes in Latin America, as well as the challenges and opportunities for improvement. Information was gleaned through a review of the literature, public databases, and conference presentations, in addition to a survey of clinical experts and patient organizations from the region. Breast cancer annual incidence (114,900 cases) and mortality (37,000 deaths) are the highest of all women's cancers in Latin America, and they are increasing. Twice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
112
3
18

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(145 citation statements)
references
References 43 publications
6
112
3
18
Order By: Relevance
“…Increasing mortality rates in Asia, Latin America, and Africa have been previously documented (38,(57)(58)(59). It has been reported that the increase in breast cancer death rates in Japan began in the 1960s, approximately 10 years after the country experienced a transition from a traditional Asian plant-based diet to a Western meat-based diet and subsequently an increase in the prevalence of overweight and obesity (58).…”
Section: Discussionmentioning
confidence: 96%
“…Increasing mortality rates in Asia, Latin America, and Africa have been previously documented (38,(57)(58)(59). It has been reported that the increase in breast cancer death rates in Japan began in the 1960s, approximately 10 years after the country experienced a transition from a traditional Asian plant-based diet to a Western meat-based diet and subsequently an increase in the prevalence of overweight and obesity (58).…”
Section: Discussionmentioning
confidence: 96%
“…Breast cancer is the leading malignant neoplasm in women in Mexico, and as in other countries of Latin America, it often appears at advanced stages with high associated mortality 9 . There are very limited data on epidemiological, clinical, histopathological, and surgical characteristics of breast cancer managed in private medicine settings where, by definition, greater access to both screening and best available treatments is generally possible.…”
Section: Discussionmentioning
confidence: 99%
“…As many as 1.2 million women worldwide are diagnosed each year, and approximately 500,000 women die annually from this disease (24). The incidence of breast cancer accounts for 7-8% of the total number of malignant tumors (25).…”
Section: Discussionmentioning
confidence: 99%